Issues of Sustainable Development in the Light of a GIS-based Assessment of the Geochemical State of the Aquatic Environment - Rozpondek, Katarzyna; Rozpondek, Rafał (Problemy Ekorozwoju, 2017)
This paper investigated issues around sustainable development in light of the assessment of the geochemical state of an aquatic environment, focussing on the accumulation of contaminants in sediments. The analysis was carried out on the concentrations of nine metals: As, Ba, Cd, Co, Cr, Cu, Ni, Pb, and Zn. Classification of results was based on geochemical criteria. The results relate to the background geochemical values characterised by natural conditions without human interference. Using GIS, maps were compiled which highlighted the spatial distribution of the contaminants, namely for the selected heavy metals (Ba, Cr, Cu, Ni, Pb and Zn). These maps enabled the relationships between these elements to be studied. Analysis of sediments contaminated by heavy metals is an important tool in environmental monitoring. The study showed that potential contamination in sediments can reach significant levels. Therefore, systematic monitoring of metal concentrations in the sediment should encompass the greatest number of reservoirs possible. This will enable ecological equilibrium to be maintained in aquatic environments. This will help to identify, eliminate, and prevent the negative effects of human economic activities which will improve the rational utilisation of environmental resources, important from the sustainable development point of view.